GAMBARAN STATUS GIZI PASIEN HIPERTENSI DI PUSKESMAS MELUR PEKANBARU - Try Intan K; Yanti Ernalia; Lilly Haslinda (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTHypertension is one of the issues that need to be prevented early on. This disease often does not cause show any symptoms, the high and uncontrolled blood pressure in long term can lead to complications. The prevalence of hypertension with obesity has increased in both the developed and developing countries. It is caused by negative changes in lifestyle that lead to metabolic changes and globalization. Patients with hypertension and obesity have higher circulating blood volume and cardiac pumping power compared to person with the ideal weight. The aim of this research is to figure out description of the nutritional status of patients with hypertension in Puskesmas Melur Pekanbaru. this is sdescriptive research where the population was all hypertensive patients who come for treatment to Puskesmas Melur Pekanbaru and the samples were taken with consecutive sampling method. The result showed that there were 87 people consist of 29.9% male and 70.1% female, the average age is at 46-65 years, 67.8% of respondents do not have a family history of hypertension and 52, 9% were hypertensive stage 1. The most common nutritional status based on a body mass index is obesity stage 1 (40.2%), followed by normal category (21.8%), overweight (20.7%), obesity stage 2 (14.9 %) and underweight (2.3%). Based on the measurement of waist circumference, 80.46% of patients were obesity and 19.54% were found not obese. Based on waist hip ratio, 90.8% of the patients were obese and 9.2% include not obese.Key words : nutritional status, hypertension, obesity, Puskesmas Melur Pekanbaru